The Problem of Evil in the Western Tradition : From the Book of Job to Modern Genetics - Kelly, Joseph F. (Joseph Francis), 1945- (Book collections on Project MUSE., 2002)
"Evil presents a profound and eternal challenge to humanity--why do we do what we know to be wrong? Why does not an all-good and omnipotent God step in and put an end to evil? [This book] looks at people's efforts to deal with evil, starting with ancient Israel and moving through the great figures of the Western tradition to the twenty-first century"--Page 4 of cover